Modelling Micro-Level Tourism Expenditure: Recommendations on the Choice of Independent Variables, Functional Form and Estimation Technique. (February 2014) - Thrane, Christer
Marcussen (2011a) distinguished between the vital and the not-so-vital determinants of micro-level tourism expenditure. Arguably, the lessons learned from Marcussen's study, combined with best practice in recent econometric modelling, have set a new higher standard for future research on this topic. Against this background, this paper gives practical advice on how to improve the modelling of micro-level tourism expenditure in the future. Three issues are discussed: (a) the choice of independent variables; (b) the choice of functional form; and (c) the choice of estimation technique. Empirical illustrations are provided.